Services for refugees subject to sexual and gender-based violence in Turkey and Sweden - Ozcurumez, S; Akyuz, S; Bradby, H (European journal of public health, 2019)
Abstract Background Sexual and gender-based violence affects an unknown proportion of Syrians seeking refuge from the ongoing conflict. Exile implies a vulnerability to gendered harms with consequent health effects over the short- and long-term. Services for refugees tend to presume physical gendered harms accruing to women prior to exile, with little attention paid to the effects on refugees’ settlement in the new society. Methods Interviews with health and social care providers of services to refugees in Sweden (n = 20) and Turkey (n = 20), including international organisations, non-government agencies, municipal and other statutory agents. Results Definitions of sexual and gender-based violence that inform service delivery vary greatly between health and social care service providers, with these definitions proving critical for how services are configured and provided. Service providers may consider longer-term health problems arising from refugees’ experience of sexual and gender-based violence, but refugees’ prospects of integration are rarely explicitly addressed. Refugees’ own views on their health and social care needs do not inform the design or development of service provision. Conclusions The experience of sexual and gender-based violence by refugees from Syria is widely recognised among health and social care providers in Turkey and Sweden. However, the experience of such violence is rarely addressed as a public health problem, that is, as a social determinant of ill health and, furthermore, an impediment to successful integration. The long-term, ill effects of sexual and gender-based violence, as seen over the lifecourse, are over-looked when considering refugees. Key messages Services for refugees who have been subject to sexual and gender-based violence vary in terms of how that violence is understood and which of its outcomes are addressed. Sexual and gender-based violence when experienced by refugees is rarely seen as a public health problem.